2019
DOI: 10.1016/j.immuni.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome Activation Triggers Blood Clotting and Host Death through Pyroptosis

Abstract: Inflammasome activation and subsequent pyroptosis are critical defense mechanisms against microbes. However, overactivation of inflammasome leads to death of the host. Although recent studies have uncovered the mechanism of pyroptosis following inflammasome activation, how pyroptotic cell death drives pathogenesis, eventually leading to death of the host, is unknown. Here, we identified inflammasome activation as a trigger for blood clotting through pyroptosis. We have shown that canonical inflammasome activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
306
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 294 publications
(317 citation statements)
references
References 63 publications
9
306
0
2
Order By: Relevance
“…The authors suggested that higher virus doses are needed to trigger complement-dependent thrombocytopenia as compared to complement-dependent inflammatory cytokine activation, which occurs after intravenous injection of even relatively low virus doses [106]. It was recently discovered that upon executing necrotic type death, macrophages release tissue factor (TF), one of the principal factors activating blood coagulation cascade [110]. It was determined that platelet activation occurs rapidly after their incubation with HAdv-C5 and that platelets express HAdv-C5 attachment receptor, CAR, suggesting that direct HAdv-C5 binding to CAR on platelets may be responsible for virus-mediated platelet activation.…”
Section: Administration; (B) DC Cell-mediated Ifn-i Production That Amentioning
confidence: 99%
See 1 more Smart Citation
“…The authors suggested that higher virus doses are needed to trigger complement-dependent thrombocytopenia as compared to complement-dependent inflammatory cytokine activation, which occurs after intravenous injection of even relatively low virus doses [106]. It was recently discovered that upon executing necrotic type death, macrophages release tissue factor (TF), one of the principal factors activating blood coagulation cascade [110]. It was determined that platelet activation occurs rapidly after their incubation with HAdv-C5 and that platelets express HAdv-C5 attachment receptor, CAR, suggesting that direct HAdv-C5 binding to CAR on platelets may be responsible for virus-mediated platelet activation.…”
Section: Administration; (B) DC Cell-mediated Ifn-i Production That Amentioning
confidence: 99%
“…Upon analysis of plasma levels of sCD62P and D-dimer, it was found that 6 h after intravenous virus administration, their concentrations were significantly higher compared to mock-treated mice, with the highest concentrations of D-dimer observed after intravenous administration of HAdv-C5, HAdv-B11, HAdv-B35, and HAdv-F41 [109]. It was recently discovered that upon executing necrotic type death, macrophages release tissue factor (TF), one of the principal factors activating blood coagulation cascade [110]. Because large numbers of Kupffer cells die via a necrotic type death after interaction with HAdv, it is plausible that Kupffer cells release TF, which activates systemic intravascular coagulation.…”
Section: Systemic Pathological Sequelae Of Adenovirusinduced Activatimentioning
confidence: 99%
“…In addition to T3SS effectors, structural T3SS components also provoke inflammasome activation. The inner rod protein EscI of the LEE‐encoded T3SS, the inner rod protein EprJ and the needle protein EprI of the E. coli type III secretion system 2 (ETT2) activate murine NLRC4 inflammasomes in vitro when introduced directly into the macrophage cytosol (Miao, Mao, et al, ; Zhao et al, ; Yang et al, ; Wu et al, ); however, the ETT2 has accumulated considerable mutational attrition and is not believed to form a functional T3SS (Ren et al, ). Critically, the EPEC T3SS needle protein EscF is one of the needle proteins that are not detected in human THP‐1 macrophages (Yang et al, ).…”
Section: Subversion Of Inflammasomes By Attaching and Effacing (A/e)mentioning
confidence: 99%
“…Activator (Knodler et al, 2014;Vanaja et al, 2016;Goddard et al, 2019) CASP4 ! NLRP3 Stx (EHEC) (Lee et al, 2016;Platnich et al, 2018) Tir and LPS (T3SSdependent) (EPEC) (Goddard et al, 2019) NLRP3 Haemolysin EhxA (EHEC) (Zhang et al, 2012;Cheng et al, 2015) Nlrp3 RNA:DNA (EHEC) (Vanaja et al, 2014) Naip2-Nlrc4 EscI (T3SS rod; EPEC/ EHEC), EprJ (ETT2 rod; EHEC) Zhao et al, 2011;Wu et al, 2019) NAIP-NLRC4 OR Naip1-Nlrc4…”
Section: Signals For Inflammasome Activationmentioning
confidence: 99%
See 1 more Smart Citation